2016
DOI: 10.1007/s10157-016-1365-6
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid attenuates renal fibrosis through the induction of autophagy

Abstract: These findings suggest that VPA may be a candidate drug for the treatment of renal fibrosis through the induction of autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…In addition, anti-fibrotic effects of valproic acid, an inhibitor of class I HDACs, have been reported in experimental models of numerous fibrotic conditions 157 . This drug suppresses TGFβ1-stimulated αSMA expression, probably by modulating SMAD expression, and is a potent inducer of autophagy 158,159 . More recently, several compounds with selectivity for individual HDACs, including HDAC1, HDAC3, HDAC6 and HDAC8, have been described 160 .…”
Section: Targets and Therapeutic Interventions For Epigenetic Changesmentioning
confidence: 99%
“…In addition, anti-fibrotic effects of valproic acid, an inhibitor of class I HDACs, have been reported in experimental models of numerous fibrotic conditions 157 . This drug suppresses TGFβ1-stimulated αSMA expression, probably by modulating SMAD expression, and is a potent inducer of autophagy 158,159 . More recently, several compounds with selectivity for individual HDACs, including HDAC1, HDAC3, HDAC6 and HDAC8, have been described 160 .…”
Section: Targets and Therapeutic Interventions For Epigenetic Changesmentioning
confidence: 99%
“…Renal interstitial fibrosis is an inevitable outcome of all causes of progressive chronic kidney disease (CKD). EMT (Pang et al, 2016), chronic inflammation (Xiao et al, 2017), oxidative stress (Qin et al, 2016), and autophagy (Kawaoka et al, 2016) are reported to be key mechanisms in the pathogenesis and progression of renal interstitial fibrosis. To study renal fibrosis in vivo and in vitro, UUO and To preliminarily explore which aspects of LncRNA 74.1 exactly exerted its functional role, the markers of inflammation (IL-6, TNF-α, MCP-1), EMT (α-SMA, E-cadherin, and vimentin), oxidative stress resistance (NQO1, HO-1) and autophagy (Atg5, Atg7, and becilin 1) were all detected in LncRNA 74.1 gain-of-function HK-2 cells with or without TGF-β treatment.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis targets of energy regulation, we can identify agents that regulate energy metabolism, such as insulin, adiponectin, and glucagon, during the process of autophagy and then change the balance of autophagy‐associated chemical reactions . Although the expression of ATGs and the formation of phagosomes are rarely influenced by these agents, they significantly change the speed and efficiency of autophagy . Furthermore, the majority of modulators targeting autophagy affect the process of autophagy induction.…”
Section: Autophagy‐associated Modulatorsmentioning
confidence: 99%
“…[282][283][284][285] Although the expression of ATGs and the formation of phagosomes are rarely influenced by these agents, they significantly change the speed and efficiency of autophagy. 286 Furthermore, the majority of modulators targeting autophagy affect the process of autophagy induction. For example, 3-MA is a phosphoinositide-3kinase (PI3K/VPS34) inhibitor widely used to suppress autophagy in basic studies, and rapamycin is an inhibitor of mTOR that leads to the formation of the autophagy initiation complex and then activates ULK1 to induce autophagy.…”
Section: Autophagy-associated Modulatorsmentioning
confidence: 99%